2002
DOI: 10.1038/sj.sc.3101263
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation facilitates functional walking in a chronic, incomplete spinal cord injured

Abstract: Design: This paper describes a treatment paradigm to facilitate functional gait in a quadriplegic, ASIA C spinal cord injured (SCI), wheelchair-dependent subject who presented with some large ®ber sensation, sub-functional motor strength in all lower limb muscles, and moderate spasticity. The study utilizes partial weight bearing therapy (PWBT) followed by epidural spinal cord stimulation (ESCS) with the assumption that both treatments would be necessary to elicit a well organized, near eortless functional gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
116
2
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(125 citation statements)
references
References 11 publications
1
116
2
6
Order By: Relevance
“…69 Electrical stimulation is known to facilitate well-being in incomplete SCI. 70 It is also important to avoid pressure palsies of peripheral nerves so that the skeletal muscles do not undergo atrophy.…”
Section: The Futurementioning
confidence: 99%
“…69 Electrical stimulation is known to facilitate well-being in incomplete SCI. 70 It is also important to avoid pressure palsies of peripheral nerves so that the skeletal muscles do not undergo atrophy.…”
Section: The Futurementioning
confidence: 99%
“…97,98 Also beginning in the 1980s, there were published reports of spinal cord stimulation with implanted epidural electrodes to improve motor function in persons with neurological conditions, 99 to elicit step-like behavior in persons with SCI, 30 and facilitate walking in persons with motor-incomplete injuries. 100 More recently, there have been reports wherein epidural stimulation has been used to increase the excitability of spinal circuits to a level that allows some volitional movement in persons with injuries clinically classified as motor complete. 101 While epidural spinal cord stimulation requires an invasive surgical procedure for the implantation of electrodes into the epidural space, more recent evidence indicates that transcutaneous spinal cord stimulation provides a non-invasive alternative for the stimulation of the spinal cord, using electrodes placed on the skin over the spine.…”
Section: Targeting Spinal Structuresmentioning
confidence: 99%
“…It has been further speculated that the normal neural circuitry within the spinal cord necessary for gait and other motor functions needs continuous maintenance by FES and/or body weight supported treadmill training (BWSTT) ambulation. 7 Others have suggested that such patterned neural activity may be important for both development and recovery of neurological functions. 8 Furthermore, there is substantial scientific evidence that shows that physical exercise not only stimulates production of endorphins, but contributes to the upregulation of brainderived neurotrophic factor (BDNF), which may promote synaptic and functional plasticity within the brain and spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…172 Other investigators have suggested that patterned neuronal activity with FES and/or BWSTT is important for development and even recovery of neurological functions 8 or by using both BWSTT and epidural spinal cord stimulation. 7,173 In general, it is now felt that the functional motor benefits of such exercise training does more than improve muscle strength and cardiovascular fitness in persons with SCI as animal studies have shown that it may also have an influence on synapses and motor neurons. 174 If and when a treatment will be found to reverse the neurological loss after SCI, it is unlikely that such treatment will result in complete reestablishment of all the descending and ascending projections within the spinal cord.…”
mentioning
confidence: 99%
See 1 more Smart Citation